Preventing avoidable hospital admission of older people - Jiwa, Moyez; Gerrish, K.; Gibson, A.; Scott, H. (Mark Allen Publishing, 2002)
The National Service Framework for Older People (Department of Health, 2001) stresses the importance of preventing unnecessary hospital admissions for older people. Such admissions arise when there is inadequate health and social support available in the community to meet the needs of this age group. This article reports on a study designed to evaluate the effectiveness of a programme of enhanced primary care support intended to reduce the risk of hospital admission for people aged 75 years and above. Nineteen patients out of a possible 322 in one GP practice were judged by GPs and district nurses to be "at risk" of avoidable hospital admission. All at-risk patients were visited by a GP or district nurse to review their needs for enhanced support, six patients subsequently accepting a referral for additional support. No statistically significant difference in the number of hospital admissions in the intervention group was observed compared with a group of patients with similar demographic characteristics but deemed not to be at such high risk, suggesting that the intervention might have been effective in reducing the number of avoidable hospital admissions.